Evaluasi Penggunaan Obat Anti-Tuberkulosis dan Clinical Outcome Pasien Tuberkulosis Ekstra Paru di Rumah Sakit Paru Dr. M Goenawan Partowidigdo - Nisa Najwa Rokhmah; Dewi Oktavia Gunawan; Whidya Ningsih (Lumbung Farmasi: Jurnal Ilmu Kefarmasian, 2025)
Extra-pulmonary tuberculosis is tuberculosis that causes involvement of organs outside the lung parenchyma. Data detected tuberculosis cases in Indonesia were 717,941 cases, about 20-25% of tuberculosis cases occurred outside the lungs. This study was a descriptive analysis with retrospective data collection conducted at RSPG. Data were analyzed by means of descriptive univariate analysis and bivariate analysis using chi-square statistics. The use of anti-tuberculosis drugs in extra-pulmonary tuberculosis patients using first-line treatment, namely: Rifampicin, Isoniazid, Pyrazinamide and Ethambuthol. The results of the Clinical Outcome analysis of 50 patients based on the parameters of clinical symptoms, body weight, BTA test results and Thorax X-rays, namely there were 40 patients (80%) who experienced improvement in clinical symptoms, 42 patients (84%) experienced weight gain, 50 patients (100%) did not experience changes in BTA test results and 36 patients (72%) who experienced improvement in Thorax X-ray examination results. The results of Chi-square analysis showed that there was a significant influence between anti-tuberculosis treatment on Clinical Outcome based on patient clinical symptoms (p<0.05).